2010
DOI: 10.3109/07420521003697494
|View full text |Cite
|
Sign up to set email alerts
|

ACRYFROM THE KRILL

Abstract: Antarctic krill (Euphausia superba) inhabit a region with strong seasonality in several parameters, such as photoperiod, light intensity, extent of sea ice, and food availability. In particular, seasonal changes in environmental light regimes have been shown to strongly influence krill metabolism, representing control signals for seasonal regulation of physiology of this key Southern Ocean species. Here, we report the identification of a cryptochrome gene, a cardinal component of the clockwork machinery in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 62 publications
(74 reference statements)
2
42
0
Order By: Relevance
“…Recent studies provide evidence that the synchronisation of krill to its environment depends upon an endogenous circadian clock (Teschke et al 2011). Such a clock would be entrained by external environmental signals and controls circardian phenotypes and also may modulate photoperiodic responses (Gaten et al 2008;Mazzotta et al 2010).…”
Section: Reduction In Physiological Function In Adultsmentioning
confidence: 99%
“…Recent studies provide evidence that the synchronisation of krill to its environment depends upon an endogenous circadian clock (Teschke et al 2011). Such a clock would be entrained by external environmental signals and controls circardian phenotypes and also may modulate photoperiodic responses (Gaten et al 2008;Mazzotta et al 2010).…”
Section: Reduction In Physiological Function In Adultsmentioning
confidence: 99%
“…The presence of food alone is not sufficient to trigger feeding activity (Atkinson et al 2002;Teschke et al 2007). Recent research indicated that endogenous (inherent) mechanisms exist to synchronise the seasonal and circadian rhythmicity of metabolic and physiological output (Teschke et al 2007(Teschke et al , 2008(Teschke et al , 2011Mazzotta et al 2010), triggered by light (Seear et al 2009;Teschke et al 2011;Brown et al 2013). On the other hand, it was clearly shown in short-term starvation experiments that food availability does play a role: even after only 18 days without food, krill switched to a mode that reduced energy consumption and initiated consumption of body lipids (Atkinson et al 2002;Auerswald et al 2009).…”
Section: Original Papermentioning
confidence: 99%
“…qPCR was performed on specimens collected in the Ross Sea at different times of the day (01:00, 06:00, 10:00, 15:00, and 18:00) during the Antarctic summer (Mazzotta et al, 2010), when they were exposed to an almost continuous 24 h photoperiod characterized by daily variations in solar irradiance (Fig. 5).…”
Section: Localization and Temporal Expression Of E Superba Opsin Tramentioning
confidence: 99%
“…The relative levels of each RNA were calculated by the 2 − ΔΔCT method (where CT is the cycle number at which the signal reaches the threshold of detection) (Livak and Schmittgen, 2001). As previously reported (Mazzotta et al, 2010;De Pittà et al, 2013), 18S was used as housekeeping gene (QuantumRNA™ 18S Internal Standards, Ambion, Austin, TX, USA). Each CT value used for these calculations is the mean of three replicates of the same reaction.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation